2008
DOI: 10.1177/0269881107081521
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of IEG mRNA in rat brain following acute treatment with clozapine or haloperidol: a semi-quantitative RT—PCR study

Abstract: Antipsychotic drugs have been shown to modulate immediate early gene (IEG) expression in rat brain regions that are associated with schizophrenia, which may be directly linked to their immediate therapeutic benefit. In this study, we analysed the expression profile of a series of IEGs (c-fos, c-jun, fra-1, Krox-20, Krox-24, arc, sgk-1, BDNF and NARP) in six rat brain regions (prefrontal cortex, hippocampus, striatum, nucleus accumbens, thalamus and cerebellum). Rats (n=5) were administered either clozapine (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…It is not clear how clozapine and lithium regulate the function of SGK-1 in this system. Previous studies show that clozapine increases SGK gene expression (mRNA levels) in rat brain (Kumari et al, 2001;Robbins et al, 2008), whereas lithium increases SGK protein phosphorylation in rat neurons (Kumari et al, 2001;Robbins et al, 2008). Our data indicate that clozapine and lithium do not increase SGK-1 expression in C. elegans.…”
Section: Discussionsupporting
confidence: 53%
“…It is not clear how clozapine and lithium regulate the function of SGK-1 in this system. Previous studies show that clozapine increases SGK gene expression (mRNA levels) in rat brain (Kumari et al, 2001;Robbins et al, 2008), whereas lithium increases SGK protein phosphorylation in rat neurons (Kumari et al, 2001;Robbins et al, 2008). Our data indicate that clozapine and lithium do not increase SGK-1 expression in C. elegans.…”
Section: Discussionsupporting
confidence: 53%
“…These effects can at least partially be reversed by appropriate antipsychotic treatment (Durany and Thome 2004). Similarly, the brain region-specific modulation of immediate-early genes and the transcription factor c-Fos may constitute a marker of antipsychotic druglike activity (Liesbeth et al 2009) and directly linked to their therapeutic benefit (Robbins et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of our ¿ ndings showed that intravenous administration of haloperidol in doses of 0.1-0.5-1.0 mg/kg (the same doses are administered to rats for studying the psychotropic effects of haloperidol, including the effects mediated by its interaction with ı-receptors [15]) does not increase the threshold of electrical ¿ brillation of the heart ventricles. Moreover, the threshold of electrical ¿ brillation tended to decrease after administration of haloperidol in all doses (Fig.…”
Section: Resultsmentioning
confidence: 87%